ANALISIS MANAJEMEN BISNIS SYARIAH STRATEGI PENGEMBANGAN BISNIS SOTO MIE BOGOR KANG JAMAL - Jamaludin R; Trihantana, Rully; Suryani, Ermi (Jurnal Penelitian Manajemen Bisnis Syariah: Program Studi Manajemen Bisnis Syariah, 2024)
A business development strategy is a method or effort taken by a company to develop the business it runs. In this case, there are several reasons that support the development of a business, including the potential for the creation and expansion of the workforce for the unemployed, to increase the income of the surrounding community, and to grow the skills possessed by the community. With the Soto Mie Bogor Kang Jamal business that implements business development strategies effectively and efficiently, it can make Soto Mie Bogor Kang Jamal's business able to empower independent communities by producing quality products that do not violate Islamic principles. Qualitative method using Spradley model research. Data analysis. The results show that the business development strategy implemented by Soto Mie Bogor Kang Jamal is a joint combination strategy, namely vertical integration strategy (forward integration strategy, backward integration strategy, and horizontal integration strategy), intensive strategy (market penetration strategy and product development strategy), and the diversification strategy applies a related/concentric diversification strategy. If analyzed with Islamic economics, the strategies applied by Soto Mie Bogor Kang Jamal in general are in accordance with the existing theory. In this case, Soto Mie Bogor Kang Jamal only focuses on general strategies, but Soto Mie Bogor Kang Jamal also does not forget things that are regulated by Islam.